Седая даль: повесть о северных удмуртах / Гильман Касимов - Касимов Гильман Гусманович (Удмуртия, 2006)
Экземпляры: чз (20171206) / Инвентарный номер: 061793 / Цена: 40.00 / Авт.знак: К 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)6